Carbon nanotube reinforced poly(trimethylene terephthalate) nanocomposites: Viscoelastic properties and chain confinement. (29th November 2018) - Aswathi, Madathinal Kunjappan; Padmanabhan, Moothetty; Mathew, Lovely; Saha, Prosenjit; Terzano, Roberto; Kalarikkal, Nandakumar; Volova, Tatiana; Thomas, Sabu
Abstract : Through a very facile route, a new class of nanocomposites involving poly(trimethylene terephthalate; PTT) and multiwalled carbon nanotubes (MWCNTs) was developed which was found to be high performance engineering material showing high modulus. Morphological, mechanical, viscoelastic, and thermal properties of the PTT nanocomposites with varying compositions of MWCNT were systematically studied and the results were analyzed. The dynamic mechanical and tensile properties of all the nanocomposites were seen to be enhanced with the addition of MWCNT and the sample containing 2 wt% MWCNT showing a storage modulus as much as 9.4 × 10 8 GPa. The results were correlated with the morphological features obtained from scanning electron microscopy and transmission electron microscopy. Coefficient of effectiveness, degree of entanglement density, and reinforcement efficiency factor were estimated from the storage modulus values and, in addition, the degree of chain confinement also could be quantified. Furthermore, theoretical modelling was also done on the elastic properties of the composites. The crystallization temperature, glass transition temperature, and percentage crystallinity were estimated for all the nanocomposites and it was found that the sample with 3 wt% MWCNT content exhibited the highest glass transition temperature of 68.2°C. POLYM. ENG. SCI., 59:E435–E445, 2019. © 2018 Society of Plastics Engineers